Antecedents Effect of Financial Inclusion for the People of North Sumatera - Adelina Lubis; Ritha Dalimunthe; Chandra Situmeang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to determine the effect of financial literacy and financial technology (fintech) partially influencing financial inclusion in the people of North Sumatra, then to determine the effect of financial literacy and financial technology (fintech) simultaneously influencing financial inclusion in the people of North Sumatra. The research samples are 100 respondents. The method of analysis in this study is multiple linear regression analysis. The results of the regression analysis partially show financial literacy and financial technology have a positive and significant effect on financial inclusion in the people of North Sumatra. Simultaneously financial literacy and financial technology affect financial inclusion in society North Sumatra. The most dominant variable affecting financial inclusion is financial literacy.